HIEGENE AND SANITATION OF WASHING HAND BY SOAP IN KEBUN BUNGA VILLAGE, SUKARAMI DISTRICT, PALEMBANG - Aziz, Zalili; Aseptianova, Aseptianova; Nawawi, Sulton; Yuliany, Eka Haryati (Institut Seni Indonesia Padangpanjang, 2019)
Hygiene and sanitation behavior of hand washing with soap is the most inexpensive and effective health investment to prevent various diseases. Washing hands with soap is a small thing but has a big impact on human health. The aim of this community service is to increase knowledge, abilities and active role of PKK, dasawisma, and the community about hygiene and sanitation hand washing with soap so that it can improve the awareness of public health. This community service uses a participatory and quantitative descriptive model to describe the behavior of the population regarding hygiene and sanitation in applying hand washing with soap. In conclusions, the community service consist of: 1) An increase od awareness in hygiene and sanitation of hand washing with soap. 2) Respondents start to realize that washing hands with soap can prevent various diseases. 3) Respondents understand and know the usefulness and important of hand washing with soap time.